ON X-SUB-LINEARLY INDEPENDENT OF ROUGH GROUPS - Yanti, Gusti Ayu Dwi; Fitriani, Fitriani (IndoMS, 2024)
In 1982, Pawlak introduced a concept, namely the rough set theory. Several studies have been conducted regarding applying rough set theory in algebraic structures such as rough groups, rough rings, and rough modules. Furthermore, X-sub-linearly independent is a generalization of linearly independent concepts. In this paper, we investigate the X-sub-linearly independent of rough groups.